The determinants of management systems implementation: Study results - Katarzyna Boczkowska; Konrad Niziołek (Economic and Environmental Studies (E&ES), 2019)
In the recent years the slowdown in the field of management system certification has been observed. There is a need to try and identify the causes of this phenomenon and the use of exploratory factor analysis may prove a very useful tool. The aim of the article is to identify the factors determining the decision to implement management system(s) in accordance with the requirements of the ISO 9001, ISO 14001 and OHSAS/PN-N 18001 standards, related barriers and the effects of the system(s) implementation. Based on the survey carried out on 36 companies with the use of CAWI technique a construct with distinguished scales for the reasons, barriers and benefits of implemented management systems was developed. The selected groups of factors allow to identify the problems more precisely. For example, 3 latent variables determined for the barriers highlighted the problems of implementing the systems connected with the documentation development, the attitudes of management and employees and system documentation implementation or combining it with the one currently existing in the organization. The presented study is an introduction to further extended research.
Keywords: L15 L23; M11; 330; ISO 9001; ISO 14001; OHSAS 18001; integrated management systems